Diabetes Mellitus Negatively Impacts Outcomes of HBV-Related Hepatocellular Carcinoma Following Thermal Ablation - Wu KC; Lee IC; Liu CA; Chiu NC; Hsu SJ; Lee PC; Wu CJ; Chi C; Luo JC; Hou MC; Huang YH (Journal of Hepatocellular Carcinoma)
Kuo-Cheng Wu,1,2 I-Cheng Lee,1,3 Chien-An Liu,4,5 Nai-Chi Chiu,3,5 Shao-Jung Hsu,1,3 Pei-Chang Lee,1,3 Chi-Jung Wu,1,3,4 Chen-Ta Chi,1,3,4 Jiing-Chyuan Luo,1,3 Ming-Chih Hou,1,3 Yi-Hsiang Huang1,3,4,6 1Division of Gastroenterology and Hepatology, Department of Medicine, Taipei Veterans General Hospital, Taipei, Taiwan; 2Division of Gastroenterology and Hepatology, Department of Medicine, Keelung Hospital, Ministry of Health and Welfare, Keelung, Taiwan; 3School of Medicine, College of Medicine, National Yang Ming Chiao Tung University, Taipei, Taiwan; 4Institute of Clinical Medicine, National Yang Ming Chiao Tung University, Taipei, Taiwan; 5Department of Radiology, Taipei Veterans General Hospital, Taipei, Taiwan; 6Healthcare and Service Center, Taipei Veterans General Hospital, Taipei, TaiwanCorrespondence: I-Cheng Lee, School of Medicine, College of Medicine, National Yang Ming Chiao Tung University, 201 Shih-Pai Road, Sec. 2, Taipei, 112, Taiwan, Tel +886-2-28712121 ext. 7506, Fax +886-2-28739318, Email iclee@vghtpe.gov.twPurpose: Diabetes mellitus (DM) negatively impacts chronic hepatitis B patients, but its role in those with HBV-related hepatocellular carcinoma (HCC) undergoing ablation remains unclear. This study aims to evaluate the influence of DM on recurrence patterns and overall survival (OS) among patients with HBV-related HCC undergoing ablation.Patients and Methods: We retrospectively enrolled 372 patients receiving thermal ablation for HBV-related HCC, including 96 (25.8%) patients with DM. Factors associated with local tumor progression (LTP), distant recurrence, and OS were analyzed. The prognostic value of DM in IMbrave050-defined high-risk population was validated.Results: DM did not correlate with LTP, whereas patients with DM had significantly higher risk of distant recurrence (median time to recurrence 23.7 versus 46.2 months, p=0.032), poorer OS (median OS 75.6 versus 106 months, p=0.011), and poorer post-recurrence survival (70.7 versus 106 months, p=0.009). In multivariate analysis, DM (hazard ratio (HR)=1.466, p=0.012), FIB-4 score, multiple tumors, and AFP level were independent predictors of distant recurrence, while DM (HR=1.424, p=0.028), ALBI score, tumor size, AFP and creatinine levels were significantly associated with OS. A DM-based risk score effectively discriminated the risk of distant recurrence. The IMbrave050 criteria could stratify the risk of LTP but not distant recurrence. DM status further discriminated the risk of distant recurrence and mortality in the IMbrave050-defined high-risk population.Conclusion: Patients with DM had an increased risk of distant recurrence and mortality after thermal ablation for HBV-related HCC, highlighting the importance of increasing awareness of DM and implementing rigorous post-ablation monitoring for diabetic HCC patients.Keywords: hepatitis B virus, hepatocellular carcinoma, diabetes mellitus, ablation, recurrence, survival